EFEKTIVITAS PELATIHAN BUDIDAYA JAMUR TIRAM TERHADAP PEMBERDAYAAN PEMUDA DI DESA AIR PETAI, KECAMATAN PUTRI HIJAU, KABUPATEN BENGKULU UTARA - Yunita, Wiwin; Ulfasari, Nia; Gusti, Ririn; Palenti, Citra Dwi (Comm-Edu (Community Education Journal), 2025)
Empowering rural youth is a vital strategy for sustainable local economic development. This study aims to describe the impact of oyster mushroom cultivation training on youth empowerment in Air Petai Village, Putri Hijau Subdistrict, North Bengkulu Regency. The training was conducted due to the low involvement of youth in productive economic activities, even though oyster mushrooms offer high nutritional value, economic potential, and simple cultivation technology. This research employed a descriptive qualitative approach using in-depth interviews, participatory observation, and documentation. The research subjects included youth from the Karang Taruna organization, training facilitators, and village officials. The results showed that the training had a positive impact on improving participants' knowledge, technical skills, and entrepreneurial motivation. Moreover, it fostered collaboration and independence in utilizing local village resources. In conclusion, this training effectively promotes youth empowerment and can be replicated in other rural areas as a strategy for local economic development.